Tinjauan Yuridis terhadap Tanggung Jawab Perusahaan Asuransi Jiwa Bersama Bumiputera 1912 Cabang Buton Kepada Pemegang Polis - Muhammad Akhsan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the legal responsibility of PT Asuransi Jiwa Bersama BUMIPUTERA 1912, Buton Branch, in fulfilling its obligations to the insured parties, as well as the legal remedies that can be pursued by the insured and the insurance company in the case at hand. The research method used is qualitative research. This study employs an empirical legal approach while delving deeper into normative legal principles. The findings reveal that AJB BUMIPUTERA has violated the applicable laws and is contractually liable for the breach of contract (wanprestasi) committed. The legal remedies available to the insured, in this case, parties B and L, include filing a lawsuit in court. Meanwhile, the legal remedy pursued by Asuransi Jiwa Bersama BUMIPUTERA 1912 is to maximize the implementation of the Financial Recovery Plan (RPK). This research contributes to a better understanding of legal protection for insurance service consumers.